¿Democratic transformation or political control? Comparative analysis of institutional citizen participation in South America - Schneider, Cecilia; Welp, Yanina (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2011)
Since the end of the 1980s, Latin America’s local governments have been experiencing a genuine political transformation. A part of this transformation implies the implementation of policies and institutions for citizen participation. Through a comparative analysis of four cases –Buenos Aires, Bogota, Caracas and Montevideo– this article explores how variables in the political context, such as citizen demand for participation, the existence of political will, the oppositional or allied relation between local and central governments, and the fragmentation and polarization of the local party system condition the origin and the reach of participatory designs present in the cities mentioned. To that end, the author proposes a typology of Institutional Citizen Participation –ICP– and some exploratory hypotheses to explain their emergence; institutions present in the case studies are systematized and connections are established between the design of the ICP and the dimensions of the political contexts analyzed; finally, conclusions are drawn.